The Impact of Empowerment Human Strategy on Enhancing the Financial Performance: Empirical study on Working Banks in Jordan - الهنيني ايمان احمد; النسور ديمة (Journal of Economics and Administrative Sciences, 2025)
This study aimed at recognizing the impact of empowerment of human resources strategy on enhancing the financial performance in working banks in Jordan, the axes of the strategy were: informative sharing, free and independence, working teams, and organizational power. To achieve the objective of the study, a questionnaire is designed and distributed on the sample of the study, which represented 60 employees of Banks. After analyzing the data by using SPSS, the study resulted that there is positive impact of empowerment of human resources strategy on enhancing the financial performance in working banks in Jordan. It suggested that the working banks in Jordan should establish database, and to create working teams.